Analysis of LMNB1 duplications in autosomal dominant leukodystrophy provides insights into duplication mechanisms and allele-specific expression - Giorgio, Elisa; Rolyan, Harshvardhan; Kropp, Laura; Chakka, Anish Baswanth; Yatsenko, Svetlana; Gregorio, Eleonora Di; Lacerenza, Daniela; Vaula, Giovanna; Talarico, Flavia; Mandich, Paola; Toro, Camilo; Pierre, Eleonore Eymard; et al. (Human mutation, 2013)
Autosomal dominant leukodystrophy (ADLD) is an adult onset demyelinating disorder that is caused by duplications of the lamin B1 (LMNB1) gene. However, as only a few cases have been analyzed in detail, the mechanisms underlying LMNB1 duplications are unclear. We report the detailed molecular analysis of the largest collection of ADLD families studied, to date. We have identified the minimal duplicated region necessary for the disease, defined all the duplication junctions at the nucleotide level and identified the first inverted LMNB1 duplication. We have demonstrated that the duplications are not recurrent; patients with identical duplications share the same haplotype, likely inherited from a common founder and that the duplications originated from intrachromosomal events. The duplication junction sequences indicated that nonhomologous end joining or replication-based mechanisms such fork stalling and template switching or microhomology-mediated break induced repair are likely to be involved. LMNB1 expression was increased in patients’ fibroblasts both at mRNA and protein levels and the three LMNB1 alleles in ADLD patients show equal expression, suggesting that regulatory regions are maintained within the rearranged segment. These results have allowed us to elucidate duplication mechanisms and provide insights into allele-specific LMNB1 expression levels.
Gesehen am 17.03.2021
Correction(s) for this article: Volume 35, Issue 1, Human Mutation, pages: 149-149
First Published online: October 28, 2013